Formulation by design-based proniosome for accentuated transdermal delivery of risperidone: in vitro characterization and in vivo pharmacokinetic study. (17th November 2015) - Imam, Syed Sarim; Aqil, Mohammed; Akhtar, Mohammed; Sultana, Yasmin; Ali, Asgar
Abstract: Aim : The aim of this work was to investigate the effects of formulation variables on the development of risperidone proniosomal formulations as potential transdermal delivery systems. Materials and methods : A 4 3 factorial design was employed to evaluate individual and combined effects of formulation variables cholesterol ( X 1 ), span 60 ( X 2 ), phospholipid G90 ( X 3 ), and risperidone ( X 4 ) added on vesicle size ( Y 1 ), encapsulation efficiency ( Y 2 ), and flux ( Y 3 ) of proniosomes. Results and discussion : The investigated risperidone-loaded proniosomal formulation shows significantly higher skin permeation in comparison to conventional liposomes with ER of 4.4 times through rat skin. The bioavailability studies in rats indicated that mean value of AUC0–48 by ROPF-TTS was 1.31 times higher than that of oral dosage form. So it could be concluded that C max value of ROPF-TTS was significantly reduced while AUC values were apparently increased. Conclusion : The developed proniosomal-based transdermal therapeutic systems incorporating risperidone would provide a useful strategy for better management of schizophrenia.